Company : the radically casual art of cooking for others - Thielen, Amy (W.W. Norton & Company, Inc., 2023)
"From beloved writer and cook Amy Thielen comes a year of inventive recipes and twenty menus for the "let's do it at my house" set-and those who aspire to it. In her much-anticipated follow-up to The New Midwestern Table, Amy writes, "no one will ever care about the food as much as you and I do." Company will have you rethinking the way you entertain, throwing dinner parties that are less formal, more frequent, and as fun for the cook as for the guests. Preaching leniency, not-guilty pleasures, and the art of making it in advance, Amy soothes the most common party anxieties one by one. Her reflections on writing menus, produce shopping, and how to time a meal are novel but timeless. Not afraid of meat (but obsessed with vegetables), these 125 loyal recipes are arranged in menu form-from intimate dinner parties to larger holiday feasts to parties that serve up to twenty. With a feast of gorgeous photography and plenty of down-in-the-pan cooking nerdery, Company encourages a return to the habit, and the joy, of cooking for family and friends"--